Technological Structure of Industrial Exports in Latin America (1990-2010) (2019)
We analyze the behavior of industrial exports from a representative sample of Latin American countries in the period 1990-2010, taking into account its technological content and contrasting it with the performance of the United States, the European Union and South Korea equivalent exports. At this time most countries of the region undertook a series of reforms in international trade, which in some cases were further deepened, while in others stagnated or were reversed. The main hypothesis of the paper is that the region presented, at the beginning of the new millennium, a process of exports diversification towards products with greater technology intensity. This process has been overshadowed, with some exceptions (Brazil, Mexico), by the expansion of trade in primary products, which recomposed the export basket in detriment of industrial products, and placed some of these countries in a precarious path of integration into the world economy. The information analyzed supports the validity of this conjecture.